The Factors Underpricing Level in The Companies Conducting Initial Public Offering At Indonesia Stock Exchange - Yohandes Rabiqy; Yusnaidi Yusnaidi (AFEBI Management and Business Review, 2017)
The purpose of this research is to examine and analyze the influence of of the variables Current Ratio, Firm Size, Financial Leverage, and Return on Equity to Underpricing level. This research used the Initial Public Offerings companies which was listed its stock to Indonesian Stock Exchange. The data that is used at this research was taken from the annual published financial report of each company. The population in this research is companies that were listed to Indonesian Stock Exchange during period 2012 through 2016. The amount of population was 115 companies. Based on certain criteria, there are 62 samples from population. Method of multiple linear regressions on panel data approach using Common Effect Model (The Pooled Least Square). Simultaneous test in hypotesis results shows that Current Ratio, Firm Size, Financial Leverage, and Return on Equity have a significant effect on the Underpricing level of Initial Public Offerings companies. Partial test (t-test) in hypothesis result shows that Firm Size have a negative and significant effect on the Underpricing level of Initial Public Offerings companies that listed in Indonesian Stock Exchange. Current Ratio, Financial Leverage, and Return on Equity have a negatif and insignificant on the Underpricing level of Initial Public Offerings companies that listed in Indonesian Stock Exchange.Keywords: Common Effect Model, Financial Leverage, Firm Size, Return on Equity, Underpricing Current Ratio